Functional outcomes after laparoscopic versus robotic-assisted rectal resection: a systematic review and meta-analysis - Kowalewski, Karl-Friedrich; Seifert, Laura; Ali, Seher; Schmidt, Mona Wanda; Seide, Svenja; Haney, Caelán Max; Tapking, Christian; Shamiyeh, Andreas; Kulu, Yakup; Hackert, Thilo; Müller, Beat P.; Nickel, Felix (Surgical endoscopy, 2021)
Surgical resection is crucial for curative treatment of rectal cancer. Through multidisciplinary treatment, including radiochemotherapy and total mesorectal excision, survival has improved substantially. Consequently, more patients have to deal with side effects of treatment. The most recently introduced surgical technique is robotic-assisted surgery (RAS) which seems equally effective in terms of oncological control compared to laparoscopy. However, RAS enables further advantages which maximize the precision of surgery, thus providing better functional outcomes such as sexual function or contience without compromising oncological results. This review was done according to the PRISMA and AMSTAR-II guidelines and registered with PROSPERO (CRD42018104519). The search was planned with PICO criteria and conducted on Medline, Web of Science and CENTRAL. All screening steps were performed by two independent reviewers. Inclusion criteria were original, comparative studies for laparoscopy vs. RAS for rectal cancer and reporting of functional outcomes. Quality was assessed with the Newcastle-Ottawa scale. The search retrieved 9703 hits, of which 51 studies with 24,319 patients were included. There was a lower rate of urinary retention (non-RCTs: Odds ratio (OR) [95% Confidence Interval (CI)] 0.65 [0.46, 0.92]; RCTs: OR[CI] 1.29[0.08, 21.47]), ileus (non-RCTs: OR[CI] 0.86[0.75, 0.98]; RCTs: OR[CI] 0.80[0.33, 1.93]), less urinary symptoms (non-RCTs mean difference (MD) [CI] − 0.60 [− 1.17, − 0.03]; RCTs: − 1.37 [− 4.18, 1.44]), and higher quality of life for RAS (only non-RCTs: MD[CI]: 2.99 [2.02, 3.95]). No significant differences were found for sexual function (non-RCTs: standardized MD[CI]: 0.46[− 0.13, 1.04]; RCTs: SMD[CI]: 0.09[− 0.14, 0.31]). The current meta-analysis suggests potential benefits for RAS over laparoscopy in terms of functional outcomes after rectal cancer resection. The current evidence is limited due to non-randomized controlled trials and reporting of functional outcomes as secondary endpoints.
Published: 05 February 2020
Gesehen am 18.05.2021